Recent advances in research imaging of osteoarthritis with focus on MRI, ultrasound and hybrid imaging - Hayashi, D.; Roemer, Frank; Guermazi, A. (Clinical and Experimental Rheumatology, 2018)
For imaging of osteoarthritis (OA), MRI plays a major role in the research setting, with compositional MRI techniques becoming increasingly more important thanks to their capacity to assess 'premorphologic' biochemical compositional changes of articular and periarticular tissues. Although radiography remains the primary imaging modality in OA clinical trials, known limitations for visualisation of OA features significantly limits the utility of radiography both clinically and in the research arena. Compositional MRI techniques can potentially supplement routine clinical MRI sequences to identify cartilage degeneration at an earlier stage when radiographs may be normal. Ultrasound can be a useful adjunct to radiography and MRI particularly for evaluation of hand OA and for the evaluation of synovitis. Emerging hybrid imaging techniques including PET/MRI and PET/CT allow evaluation of the joint with simultaneous assessment of morphological changes and metabolic activities, showing a potential for these hybrid systems to play an increasing role in OA research.
EVALuna2:36263